Continuous positive airway pressure failure in the management of neonatal respiratory distress in a resource limited setting: a prospective observational study - Noor Sameer Yahya; Ahmed Khalil Ibrahim; AWS AL-NUMAN (Medicinski glasnik, 2026)
Aim: To determine the frequency and identify predictors of Continuous positive airway pressure (CPAP) failure in neonates of varying gestational ages in a resource-limited setting, where CPAP is often used beyond the preterm population. Methods: prospective observational study of 119 neonates started on CPAP within 24 hours of birth for respiratory distress. We collected Demographic, clinical, and perinatal data. CPAP failure was defined by persistent hypoxia or severe respiratory distress despite maximal settings, necessitating mechanical ventilation. Univariate and multivariable binary logistic regression analyses identify predictors of CPAP failure. Results: The CPAP failure rate was 33.6%. Univariate analysis identified lower gestational age ( ? 30 weeks), lower birth weight (?1200 g), female sex, vaginal delivery, and a 5-minute Apgar score < 7 as significant predictors. However, in the multivariable model, only a 5-minute Apgar score < 7 remained an independent predictor (Adjusted Odds Ratio AOR 5.315; p=0.006). Antenatal corticosteroid, age at CPAP initiation, and initial Fraction of inspired oxygen (FiO) ₂ were not significant. Neonates with birth weight <1200g had shorter duration of successful CPAP use as revealed by Kaplan-Meier survival analysis (p<0.001) Conclusion: This study confirms that CPAP failure is a frequent and serious problem in our resource-limited NICU. A low 5-minute Apgar score is a significant predictor of failure. To save more newborns, we must focus on improving neonatal resuscitation and make clear guidelines for respiratory care in our specific context.
Keywords: Apgar Score; Continuous Positive Airway Pressure; developing countries; Respiratory Distress Syndrome; newborn